Relationship between Consumer Competency, Value, Susceptibility to control, Communication and Coproduction in MTN in Zaria Local Government of Kaduna State - Abubakar Monsurat; Abubakar Shehu; Nura Audi Usman (Research Synergy Foundation, 2022)
The study examines relationship between Consumer Competency, Value, Susceptibility to control, Communication and Coproduction using MTN in Zaria Local Government of Kaduna State as unit of analysis. Survey research was used, 400 questionnaires were distributed to MTN users in Zaria Local Government, out of which 368 were returned and 364 were valid. The findings show that there is relationship between Competency, Susceptibility to control, Communication and Coproduction in MTN in Zaria Local Government with significance of .000, .001 and .005. While the relationship between Value and Coproduction was rejected with .407 significant. The study recommends Customers should be given opportunity to say their views and communication between Customers and MTN should be enhanced.